VD_FINDINFO HC / 2014 / 132 vom 11. Februar 2014 - VD Tribunal cantonal (2014)
OBLIGATION D'ENTRETIEN, TRAIN DE VIE, MESURE PROVISIONNELLE, DIVORCE, COMPLÉMENT | 163 CC, 176 al. 1 ch. 1 CC, 179 CC, 276 CPC (CH), 317 CPC (CH)